PENGARUH PENERAPAN TEKNOLOGI INFORMASI DAN INOVASI TERHADAP KINERJA (STUDI PADA UMKM KABUPATEN ROKAN HILIR RIAU) - desmiyawati, desmiyawati; Nasir, Azwir; Hariadi, Hariadi; Safrizal, Safrizal (Jurnal Al-Iqtishad, 2023)
The Covid-19 pandemic has greatly impacted MSMEs where many MSMEs have experienced a decline in performance and even closed. In the new normal era, MSMEs are slowly starting to rise, business actors are utilizing online media or the use of technology and innovating to boost sales again. The goal of the research is to analyze the impact of information technology and innovation on MSMEs performance in the Rokan Hilir Regency of Riau. There are 34,036 registered MSMEs in the Rokan Hilir regency, according to the Regency Office of Cooperatives and MSMEs. In contrast, the study's sample size was determined using the Slovin and criterion-based sampling methods, and it totaled 100 MSMEs. The information gathered is called "primary data," and it consists of questionnaires and interviews with a small number of MSMEs participants. The data was analyzed using a robust linear regression model. The findings of the research hypothesis indicate that information technology and innovation have a positive and significant impact on MSMEs performance. MSMEs will find it much simpler to market their products with the help of information technologies such as the use of online media, expanding the reach of their product sales. Similarly, innovative approaches to the products the company manufactures give it an edge over the competition and boost MSMEs performance.